ANALISIS LAPORAN KEUANGAN PERUSAHAAN PT KALBE FARMA TBK DALAM MENILAI KINERJA PERUSAHAAN PADA PERIODE 2017-2021 - Maylizza Putri Dyansah; Novi Darmayanti (J-MACC, 2022)
A This study was conducted with the aim of assessing the company's performance of PT Kalbe Farma Tbk in the Pre- and during Covid-19 Era by analyzing the Financial Ratio of the Annual Report for the period 2017 - 2021. The type of research used is quantitative descriptive research. The data source used is the Annual Report of PT Kalbe Farma Tbk for the period 2017 – 2021. The results of the study obtained that the company PT Kalbe Farma Tbk in 2019 - 2020 experienced a decrease in terms of liquidity ratio, namely the current ratio, cash ratio, and quick ratio due to an increase in the number of liabilities in the company. Then in terms of the ratio of solavbility (leverage) financial performance on assets and equities to liquidity increased. The activity ratio shows that the company experienced a decrease in fixed asset turnover and in inventory and total assets increased. And for the profitability ratio, the company experienced an increase in ROE and NPM.